LEGAL FEATURES AND INDUSTRY APPLICATION OF GREEN CLAUSES (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This article examines the essence, legal characteristics, and application practice of green clauses in commercial contracts. It outlines how environmental obligations are integrated into agreements across sectors and analyzes the key legal aspects of enforceability and implementation. The study demonstrates how green clauses are influencing business practices and promoting sustainability in diverse industries.